Efficacy and Adverse Events in Metastatic Melanoma Patients Treated with Combination BRAF Plus MEK Inhibitors Versus BRAF Inhibitors: A Systematic Review - Greco, Austin (Cancers (Basel), 2019)
We reviewed the literature to assess the efficacy and risk of constitutional, cardiac, gastrointestinal, and dermatological toxicities of combined BRAF plus MEK inhibitors versus BRAF inhibitors alone in patients with metastatic melanoma with BRAF mutations. Searches were conducted in PubMed, Cochrane Database of Systematic Reviews, Google scholar, ASCO, Scopus, and EMBASE for reports published from January 2010 through March 2019. Efficacy, including progression-free survival (PFS) and overall survival (OS) rates, were assessed by hazard ratio (HR); objective response rates (ORR) were assessed by odds ratio (OR). The randomized clinical trials (RCTs) with comparison to vemurafenib monotherapy were included to determine constitutional, gastrointestinal, cardiac, and dermatological toxicities using PRISMA statistical analysis with relative risk (RR) for equal comparison to avoid inclusion bias. Five RTCs comprising 2307 patients were included to assess efficacy, while three of the five RCTs comprising 1776 patients were included to assess adverse events. BRAF plus MEK inhibitor combination therapy demonstrated overall better efficacy compared to BRAF inhibitor monotherapy. Combination therapies appear to have favorable dermatologic side effect profiles, similar constitutional and cardiac profiles, and slightly worse gastrointestinal profiles compares to monotherapy regimens.